Syed Muhammad Naquid Al-Attas' Thoughts on the Urgency of Faith in Science - Ibnu Laksana Aulia Ramdani (Penerbit Hellow Pustaka, 2024)
. This article discusses Syed Muhammad Naquid Al-attas' thoughts about the urgency of faith in science. This research uses the library research research method, where data collection is carried out by searching for information through books, scriptures, journals, articles and other literature with the aim of analyzing Syed Muhammad Naquid Al-alatas' thoughts about the urgency of faith in science. The results of the research are, Naquib defines knowledge from an epistemological point of view as arriving at the meaning of something in the soul and the soul arriving at the meaning of something. Faith according to al-Attas is more than knowledge, knowledge in Islam has a worldly and spiritual dimension. Knowledge summarizes true belief and belief (iman), knowledge and faith are one thing in Islam because in order to reach or understand the truth of Islam, knowledge is needed. Islam is a religion based on faith and knowledge, and these two important elements strengthen each other. Syed Muhammad Naquib Al Attas said that the problems that occur within Muslims and the damage to their souls are actually caused by a lack of knowledge and a lack of faith.